Elevated preoperative controlling nutritional status (CONUT) scores as a predictor of postoperative recurrence in gastrointestinal stromal tumors. Issue 7 (1st August 2022) - Yang, Weili; Shou, Chunhui; Yu, Jiren; Wang, Xiaodong; Zhang, Qing; Yu, Hang; Lin, Xianke
Abstract: Background: The controlling nutritional status (CONUT) score is associated with the postoperative outcomes in various types of tumors, and its prognostic role in gastrointestinal stromal tumors (GISTs) needs to be clarified. Methods: Patients with completely resected primary GISTs in the absence of imatinib adjuvant therapy were included. Recurrence‐free survival (RFS) was estimated with the Kaplan–Meier method and compared using log‐rank test. Prognostic factors were compared using Cox proportional hazards model. Results: A total of 455 patients were included. The median follow‐up time was 132.0 months (range: 7.0–253.0). Recurrence/metastasis developed in 92 (20.2%) patients. Patients were assigned to three groups: 219 (48.1%) were in normal nutrition group (CONUT = 0–1), 196 (43.1%) were in mild malnutrition group (CONUT = 2–4) and 40 (8.8%) were in moderate–severe malnutrition group (CONUT ≥ 5). Nongastric primary tumor site, large tumor size, high mitotic index, tumor rupture and high CONUT score were independent prognostic factors for shorter RFS using multivariate analysis ( p  < 0.05). Conclusions: Elevated preoperative CONUT score was a predictor of recurrence for patients with resected GIST. The clinical application of the CONUT score is simple and feasible, and might contribute to the individualized treatment of GIST patients.